Influence of Renewable Energy Sources on Electricity Transmission Networks in Central Europe - Karel Janda; Jan Malek; Lukas Recka (Charles University in Prague, Institute of Economic Studies (IES), 2017)
This paper focuses on the influence of increased wind and solar power production on the transmission networks in Central Europe. The model ELMOD is employed. Two development scenarios for the year 2025 are evaluated on the basis of four representative weeks. The first scenario focuses on the effect of Energiewende on the transmission networks, the second one drops out nuclear phase-out and thus assesses isolated effect of increased feed-in. The results indicate that higher feed-in of solar and wind power increases the exchange balance and total transport of electricity between transmission system operator areas as well as the average load of lines and volatility of flows. Solar power is identified as a key contributor to the volatility increase, wind power is identified as a key loop-flow contributor. Eventually, it is concluded that German nuclear phase-out does not significantly exacerbate mentioned problems.
Keywords: L94; Q21; Q48; C61; 330; Energiewende; RES; transmission networks; congestion; loop flows; ELMOD; Central Europe